Financial Development and Poverty Alleviation : Issues and Policy Implications for Developing and Transition Countries - Prokopenko, Vassili (IMF Working Papers; Working Paper, 2001)
This paper reviews current thinking on the relationship between financial development and poverty alleviation-a subject that has grown increasingly important in the policy prescriptions of the IMF and other international financial institutions in recent years. Although work on this issue is far from over, some important lessons can be learned from the existing evidence. The paper reflects on these lessons and looks at some of the policy implications of the analysis.